A política energética alemã [recurso eletrónico] : exemplo europeu de sustentabilidade? - Boura, Ana Isabel (2019)
The energy transition to renewable energies has been a prime objective in the government policy of reunified Germany. In the concerted action of various ministries, important measures have been taken to gradually replace fossil and nuclear fuels with renewable energy. To state investment in energy production, distribution and storage the German government adds support to energy consumers, who thus benefit from extensive information and incentive programs. Such governmental effort to use regenerative energies is not limited to the internal plane: in meetings of international institutions, as well as through cooperation projects, the Federal Republic of Germany shares with countries on all continents the successful experience of its new energy policy.